Emerging understandings of mindfulness through experiential awareness. (2nd January 2018) - Higgins, Joanna; Eden, Raewyn
ABSTRACT: Mindfulness practices are increasingly used in classrooms to enhance the well-being dimensions of learning environments. New Zealand policy documents draw on a bicultural perspective that promotes a holistic framing of well-being. This paper will consider the transformative possibilities of a mindfulness-based breathing intervention in two New Zealand classrooms of students aged between 10 and 12 years old. Operational definitions of mindfulness include awareness of emotional, cognitive, and physical experiences rather than a focus on a state of mind. Using authentic inquiry, we draw on multi-theoretical and multi-methodological perspectives to explore observing/noticing/attending to sensations/perceptions/thoughts/feelings associated with a classroom mindfulness intervention. Specifically, we examine students' increased awareness and evolving understandings of mind | body connections that emerged during cogenerative dialoguing. We found that students puzzled over whether it is possible to separate physical, mental and emotional states. We consider the implications of the mindfulness-breathing intervention in generating participants' insights into well-being and wellness.